Biological and behavioral aspects of two laboratory strains of Ceratitis capitata (Diptera: Tephritidae): the influence of periodic introduction of wild flies in the colony - Joachim-Bravo, Iara Sordi; Moreira da Silva Neto, Alberto; Simões Dias, Vanessa (Instituto de Ecología, A.C., 2009)
The healthy maintenance of insects reared under laboratory conditions requires strategies to retain the natural characteristics of their life-histories traits. Rearing strategies include artificial selection to laboratory conditions, hybridization with compatible strains, and supplying the colony with wild individuals. We compared behavioral as well as life-history aspects of two laboratory strains of Ceratitis capitata Wiedemann (Diptera, Tephritidae) that had either been reared for 15-20 years under laboratory conditions with or without introducing wild specimens (Lab-Pop and Hybrid-pop, respectively). The parameters evaluated were: performance and food ingestion of immatures, adult size and longevity, female oviposition preference and fecundity, egg viability, and mating choice. Analyses of these parameters were conducted under laboratory rearing conditions. The largest differences observed between the two strains were related to behavioral components: food ingestion rate at the larval stage and oviposition behavior. In general, Lab-Pop individuals were less selective and more adapted to the artificial diet than Hybrid-Pop individuals (diet consumption), but there were no significant differences between the two strains in terms of percentage of emergence, egg viability, adult size, fecundity, and mating choice. It is suggested that the use of hybrid strains is more appropriate than the use of strains without the incorporation of wild individuals, especially in studies that involve behavioral parameters, as hybrid strains behave very similarly to wild populations, according our previous studies.